The Vigil of Quebec - Dumont, Fernand (Book collections on Project MUSE., 1974)
This book was first published in French in the wake of events which have come to be known in Quebec as the 'October crisis of 1970.' Dumont's thoughtful reflections on Quebec's social and political life invite 'les Anglais' to a new view of Quebec.